Locomotor sensitization to EtOH: contribution of β-Endorphin - Dempsey, Stephani; Grisel, Judith E. (Frontiers in Molecular Neuroscience, 2012)
Alcohol use disorders, like all drug addictions, involve a constellation of adaptive changes throughout the brain. Neural activity underlying changes in the rewarding properties of alcohol reflect changes in dopamine transmission in mesolimbic and nigrostriatal pathways and these effects are modulated by endogenous opioids such as b-Endorphin. In order to study the role of b-Endorphin in the development of locomotor sensitization to repeated EtOH exposure, we tested transgenic mice that vary in their capacity to synthesize this peptide as a result of constitutive modification of the Pomc gene. Our results indicate that mice deficient in b-Endorphin show attenuated locomotor activation following an acute injection of EtOH (2 g/kg) and, in contrast to wildtype mice, fail to demonstrate locomotor sensitization after 12 days of repeated EtOH injections. These data support the idea that b-Endorphin modulates the locomotor effects of EtOH and contributes to the neuroadaptive changes associated with chronic use.